標題:
Maths F4...2
發問:
此文章來自奇摩知識+如有不便請留言告知
Question link : http://img708.imageshack.us/img708/4521/002xys.jpg *要解釋/步驟...THX:)* 更新: http://img708.imageshack.us/img708/4521/002xys.jpg
最佳解答:
8 (2x+y) ∝ (x-2y) Let (2x+y)=k(x-2y) Then (2-k)x=-(2k+1)y => I is trueSince x+y=[(2k+1)/(k-2)]y+y=[(3k-1)/(k-2)]y x-y=[(k+3)/(k-2)]y =>II is trueSimilarly III is true because we can represent x as a function of yANSWER:E11 f(x)=Q(x)(x+4)+R f(x-4)=[Q(x-4)]x+R=[Q(x-4)](x+4)+R-4Q(x-4) So Sub x=-4 will give the remainder R-4Q(-8)=f(-8)ANSWER:B12 f(-1)=0. Set x=-1, f(2x+1)=f(-1)=0 So x+1 is a factor of f(2x+1)ANSWER:B
其他解答:
文章標籤
全站熱搜